2018
DOI: 10.1002/ptr.6019
|View full text |Cite
|
Sign up to set email alerts
|

Phlorotannin supplement decreases wake after sleep onset in adults with self‐reported sleep disturbance: A randomized, controlled, double‐blind clinical and polysomnographic study

Abstract: Our previous study demonstrated that phlorotannin supplement had a sleep-promoting effect in rodents. In the present study, we investigated whether the phlorotannin supplement could improve sleep in subjects with self-reported sleep disturbances. In a randomized, double-blind, placebo-controlled trial, 24 subjects consumed either a placebo or phlorotannin supplement (500 mg/day) for 1 week, 30-60 min prior to bedtime. Sleep parameters were assessed at baseline and at 1 week with sleep questionnaires and polyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 31 publications
(35 reference statements)
2
29
0
Order By: Relevance
“…Over the last decade, the biological properties of phlorotannins have been widely investigated, and research on phlorotannins is steadily growing. In our previous studies [ 11 , 17 ], the sleep-promoting effects and GABAergic signaling mechanisms of phlorotannins were demonstrated for the first time. Phlorotannin preparations have been shown to significantly decrease sleep latency and increase NREMS in C57BL/6N mice via the GABA A -BZD receptors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, the biological properties of phlorotannins have been widely investigated, and research on phlorotannins is steadily growing. In our previous studies [ 11 , 17 ], the sleep-promoting effects and GABAergic signaling mechanisms of phlorotannins were demonstrated for the first time. Phlorotannin preparations have been shown to significantly decrease sleep latency and increase NREMS in C57BL/6N mice via the GABA A -BZD receptors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sleep-promoting effects of phlorotannin supplements at 500 mg/kg were comparable to those of the positive control, diazepam at 6 mg/kg [ 11 ]. In addition, in a randomized, double-blind, placebo-controlled clinical trial of 20 volunteers [ 17 ], phlorotannin supplements significantly decreased wakefulness after sleep onset (phlorotannin vs. placebo, −25.5 ± 30.5 vs. −1.7 ± 14.9; p = 0.045) and total wake time (phlorotannin vs. placebo, −0.9 ± 3.0 vs. −6.1 ± 6.8; p = 0.048) compared to the placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The methods employed to measure sleep outcomes varied across studies. Seven studies used subjective measures (i.e., diaries/logbooks and sleep questionnaires) [31][32][33][34][35][36][37], while one study used PSG/EEG [38,39], and five studies used a combination of PSG/EEG or actigraphy, and subjective measures [39][40][41][42][43].…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…However, the ingestion of pure resveratrol (a stilbenoid) elicited no effect on sleep in young adults over a 28-day period [36]. On the other hand, it was found that a group of poor sleepers who were administered phlorotannin (a supplement derived from brown seaweed) experienced decreased waking after sleep onset and total wake time compared with those administered the placebo [41].…”
Section: Polyphenolsmentioning
confidence: 99%
“…In our previous studies [12,13,14], we reported the sleep-promoting effects and action mechanism of phlorotannins. A standardized phlorotannin supplement (PS, 500 mg/kg, administered per os (p.o.))…”
Section: Introductionmentioning
confidence: 99%